Digital Airlines: MyTravelling - Mahdzar, Mazlina; Mostakim, Mahfuzah; Nor Hisham, Nurul Ashikin; Zabidi, Nurul Hanis; Mohd Yatim, Siti Nornadia; Azhar, Nurul Atiqah (Multidisciplinary Applied Research and Innovation, 2021)
: MyTravelling Apps is a digital technology application of airlines. Since we are in the Pandemic Covid-19 era, the idea for this application was developed with the aim of giving users the opportunity to travel by applying the new norm through the application using the handphone. In this application, we provide some unique features among which are temperature trackers among the travellers, digital passport processes and queries, flight schedule checker and also distance tracker. This software helps to reduce physical interactions as well as provide information using its flight schedule feature.